2021
DOI: 10.2147/idr.s331249
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial-Susceptibility Profiles of Salmonella in Smallhold Broiler Supply Chains in Central Ethiopia

Abstract: Purpose Salmonellosis is a foodborne zoonoses found worldwide. The main purpose of this study was to isolate and identify Salmonella and assess their antimicrobial susceptibility profiles from smallhold broilers supply chains and slaughterhouses in Bishoftu and Modjo, central Ethiopia. Methods Four smallhold broiler farms under the auspices of Chico Meat were selected randomly. Feed, water, and water- and feed-trough samples were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
2
2
Order By: Relevance
“…The resistance towards ampicillin in this study was extremely higher than that reported for Enterococci elsewhere in Ethiopia [30]. The overall resistance towards ampicillin was lower than the reports from elsewhere [31,32] but significantly higher than the other reports [16]. The reason for high resistance towards ampicillin and also others might be due to overuse of these antibiotics [33].…”
Section: The Antibiotic Resistance Of Bacterialcontrasting
confidence: 67%
See 1 more Smart Citation
“…The resistance towards ampicillin in this study was extremely higher than that reported for Enterococci elsewhere in Ethiopia [30]. The overall resistance towards ampicillin was lower than the reports from elsewhere [31,32] but significantly higher than the other reports [16]. The reason for high resistance towards ampicillin and also others might be due to overuse of these antibiotics [33].…”
Section: The Antibiotic Resistance Of Bacterialcontrasting
confidence: 67%
“…The overall resistance (56.7%) of gram-negative isolates to ceftriaxone was also lower than that reported from the study in Rewand Referral Hospital where out of 241 gram-negative isolates tested for ceftriaxone, 75.9% had been resistant [40]. The resistance of Salmonella species towards the overall antibiotics tested was 55.6% which was comparable with 54.55% which was the resistance of the same species reported from elsewhere in Ethiopia [31]. In contrast, it was lower than the report from Bangladesh, 62.94% [41].…”
Section: The Antibiotic Resistance Of Bacterialmentioning
confidence: 41%
“…Salmonella expressed 80% resistance against chloramphenicol and neomycin disagreeing with Sohail et al (2021) who found a low resistance to these antibiotics by salmonella isolates in Afghanistan, this may be explained by high use level of these antibiotics in Egypt, this study found a low resistance against gentamycin (20%) disagreeing with Mohammed et al (2020) and agreeing with Belachew et al (2021) who stated that salmonella isolated were sensitive to Gentamycin.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, Abatcha et al reported that all their isolates were sensitive to ciprofloxacin [ 41 ]. In other countries, such as Egypt and Ethiopia, the resistance rates were 30.8% and 29.3%, respectively [ 57 , 58 ]. However, the resistance rate was comparatively lower in China (12.5%) [ 55 ], possibly due to good food hygiene practises in retail meat, with effective surveillance systems in supermarkets and open-air markets.…”
Section: Discussionmentioning
confidence: 99%